2013
DOI: 10.1177/1553350613480855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraperitoneal Bevacizumab Administration on Colonic Anastomosis and Early Postoperative Adhesion Formation

Abstract: IP administration of bevacizumab effectively reduced the formation of adhesions and caused significant impairment of anastomotic wound healing when standard doses were administered (5 mg/kg), but the 2.5-mg/kg dosage did not affect the anastomotic wound healing and also effectively reduced the formation of adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
1
18
0
4
Order By: Relevance
“…The IP adhesion-reducing effect of IP bevacizumab therapy has been demonstrated in our previous study (7). In this study, we observed that IP cetuximab application reduces early postoperative adhesions in both application types (peroperative and twenty-four hours after the operation).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The IP adhesion-reducing effect of IP bevacizumab therapy has been demonstrated in our previous study (7). In this study, we observed that IP cetuximab application reduces early postoperative adhesions in both application types (peroperative and twenty-four hours after the operation).…”
Section: Discussionsupporting
confidence: 62%
“…In the pertinent literature, there are a small number of studies investigating the effects of intraperitoneally administed new chemotherapeutic agents on anastomotic healing and on development of early adhesion formation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in animal studies that it does not affect wound or anastomotic healing, decreases the adhesion rate, and does not increase the morbidity and mortality with surgery. [25][26][27][28] On analysis of the clinicopathological variables, various variables, such as a lower PCI score, higher age at diagnosis, shorter duration of surgery, and use of HIPEC amongst others, were found to be associated with improved overall and disease-free survival. Older age seemed to be associated with improved survival.…”
Section: Discussionmentioning
confidence: 98%
“…26,27 In addition, due to the notion that bevacizumab remains in the circulation for up to 6 weeks, 22 it seems that the time lapse between the first and second surgeries in the current study allowed enough time for the bevacizumab to prevent development of adhesions after first operation, that is, reabsorbed circulating bevacizumab could affect process of adhesion maturation at the first days after first surgery, 28 so the difference in the adhesion score on the 42 postoperative day may not have resulted from a delay in adhesion formation in the bevacizumab group, which means that the difference might not disappear in a chronic phase, long after the elimination of bevacizumab in the blood. Despite being reported that wound healing complications including ecchymosis, surgical site bleeding, breakdown in anastomotic wound healing, and wound infection may occur due to bevacizumab treatment and VEGF inhibition, 29,30 it is stated in the literature that bevacizumab when administered in a low dose (2.5 mg/kg) but not a high dose (5 mg/kg) would have an acceptable toxicity profile 31 and might possibly minimize wound healing complications by reducing the inflammation involved in postoperative adhesion formation. 22,32 So, further studies are needed to evaluate the risk of wound healing complications caused by bevacizumab.…”
Section: Discussionmentioning
confidence: 99%